2019
DOI: 10.3892/ol.2019.10597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KIF2A on the prognosis of nasopharyngeal carcinoma and nasopharyngeal carcinoma cells

Abstract: Nasopharyngeal carcinoma (NPC) is a common tumor in south China. Kinesin family member 2A (KIF2A) belongs to the kinesin-13 family and is associated with the growth and invasion of a number of different types of human cancer, including ovarian, breast and prostate cancer. The aim of the present study was to evaluate the expression of KIF2A in NPC and explore the relationship between KIF2A and the basic characteristics of 5-8F cells. Immunohistochemistry was performed on tissues from 97 patients with NPC to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
(35 reference statements)
2
9
0
Order By: Relevance
“…Programmed cell death was shown to be increased in many mouse models of microcephaly ( Poulton et al, 2011 ; Little and Dwyer, 2019 ), and, in contrast, a reduction of apoptosis leads to increased brain size ( Kuida et al, 1998 ). Additionally, previous studies have already reported the correlation between KIF2A inactivation and induced apoptosis in cancer cells ( Zhang et al, 2016 , 2019 ; Li et al, 2019 ). The silencing of KIF2A by siRNA resulted in a decrease of PI3 kinase/Akt expression and downstream proteins, a key signaling pathway involved in the regulation of cell proliferation and growth, and ultimately in the initiation of apoptosis ( Wang et al, 2014 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 84%
“…Programmed cell death was shown to be increased in many mouse models of microcephaly ( Poulton et al, 2011 ; Little and Dwyer, 2019 ), and, in contrast, a reduction of apoptosis leads to increased brain size ( Kuida et al, 1998 ). Additionally, previous studies have already reported the correlation between KIF2A inactivation and induced apoptosis in cancer cells ( Zhang et al, 2016 , 2019 ; Li et al, 2019 ). The silencing of KIF2A by siRNA resulted in a decrease of PI3 kinase/Akt expression and downstream proteins, a key signaling pathway involved in the regulation of cell proliferation and growth, and ultimately in the initiation of apoptosis ( Wang et al, 2014 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 84%
“…KIF2A exerts a key role in the regulation of microtubule dynamics in the process of mitosis [ 41 , 42 ]. Researchers had proved that KIF2A served as an oncogene in a series of tumors, such as nasopharyngeal carcinoma [ 22 ], lung adenocarcinoma [ 43 ], gastric cancer [ 44 ], and glioma [ 45 ]. Wang et al disclosed that KIF2A was associated with poor prognosis of BC patients, and KIF2A silencing curbed migration and proliferation of BC cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…KIF2A, a member of the kinesin-13 family, belongs to M-type nonmotile microtubule depolymerase [ 20 ]. KIF2A has been reported to be upregulated in many tumor tissues [ 21 , 22 ]. In addition, we discovered that KIF2A may be a target of miR-603 using the miRDB database ( http://mirdb.org/ ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, KIF2A promotes malignant behaviors of oral squamous carcinoma cells via activating the PI3K/AKT signaling pathway ( 13 ). Furthermore, KIF2A induces cell proliferation and invasion, while suppressing cell apoptosis in nasopharyngeal carcinoma ( 14 ). Within clinical practice, KIF2A exhibits key prognostic value for the management of gastric cancer, colorectal cancer and nasopharyngeal carcinoma ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%